Artificial Intelligence for Blokus Classic using Heuristics, FloodFill, and Greedy Algorithm - Hong Liang Cai; Sebastian Aldi; Winston Renatan (Journal Information System Development (ISD), 2021)
Blokus is an abstract strategy game which has complex variable to determine ones move. We propose an idea for Artificial Intelligence in Blokus using Heuristics, FloodFill, and Greedy algorithm, which will be called as LeakyAI. Both the game and its implementation are established in Java language. To test the result, we performed benchmarking towards Brute Force AI, itself, and the developers.Blokus merupakan sebuah game strategi abstrak yang memiliki variabel kompleks untuk menentukan pergerakan pemain. Kami mengusulkan ide Kecerdasan Buatan pada Blokus dengan Algoritma Heuristik, FloodFill, dan Greedy, yang akan disebut LeakyAI. Baik game maupun implementasinya dibuat menggunakan bahasa Java. Untuk menguji hasilnya, kami melakukan pembandingan terhadap Kecerdasan Buatan Brute Force, dirinya sendiri, dan dengan para pengembang.